RETRACTED: Intelligent Recognition of Component Building Elements in Assembly Buildings with BIM-based Virtual Point Cloud Dataset - Huang Yihao (E3S Web of Conferences)
Following the publication of the Retraction Notice, this article has been formerly retracted on 9 June 2025. This paper has been formally retracted from publication because the author has identified significant methodology and calculation errors in the study, which affect the reliability of the conclusions and results. The request was made by the author, who apologizes for the inconvenience caused. Request approved by the Publisher on June 4, 2025.